Performance and carrier transport analysis of In0.7Ga0.3As quantum-well MOSFETs with Al2O3/HfO2 gate stack. (September 2016) - Son, Seung-Woo; Park, Jung-Ho; Baek, Ji-Min; Kim, Jin Su; Kim, Do-Kywn; Shin, Seung Heon; Banerjee, S.K.; Lee, Jung-Hee; Kim, Tae-Woo; Kim, Dae-Hyun
Highlights: We fabricated In0.7 Ga0.3 As QW MOSFETs with Al2 O3 /HfO2 gate stack. Fabricated devices shows excellent transconductance characteristics at L g  > 1 μm region. We carried out analytical modeling on intrinsic and extrinsic transconductance. Abstract: In this paper, we have fabricated and characterized In0.7 Ga0.3 As quantum-well (QW) metal-oxide-semiconductor field-effect-transistors (MOSFETs). We have employed the gate dielectric of the Al2 O3 /HfO2 (0.6/2 nm) bi-layer stack by ALD. The fabricated device with L g  = 4 μm exhibits a record maximum transconductance ( g m_max ) in excess of 520 μS/μm at >1 μm region, and reasonably good electrostatic integrity, such as SS = 110 mV/decade and DIBL = 43 mV/V. Also, we have investigated the gate length scaling behavior in terms of output, transconductance, and transfer characteristics. In particular, our devices feature very uniform values of the electrostatic integrity, such as SS = 100–110 mV/decade, V T  = −0.25 V to −0.2 V and DIBL = 40–50 mV/V, as L g decreases from 10 μm to 4 μm. Furthermore, we have explored the impact of source resistance ( R S ) onto the device characteristics of the InGaAs QW MOSFETs. In doing so, we have modeled both measured extrinsic transconductance ( g m_ext ) and intrinsic transconductance ( g m_int ) as a function of L g .